Design of A Web-Based Marketing Data Information System to Improve Product Marketing Efficiency at CV San Amerta Romoro - Anur Rahmah Tiawulandari; Ahmad Holidin; Haryanto Haryanto; Andri Cahyo Purnomo; Mohammad Fauzan Nawawi (Technema: Journal of Intelligent Engineering and Computing, 2026)
Effective marketing activities require centralized, structured, accurate, and accessible information. CV San Amerta Romora previously managed government institution data, vendor information, product data, Inaproc links, company profiles, and brochures through separate files and storage media, creating difficulties in data retrieval, updating, and information consistency. This study aimed to design a web-based marketing data information system to improve the efficiency of internal marketing information management. Data were collected through observation, interviews, and literature review, while the existing system was analyzed using the PIECES framework. System requirements were modeled using Unified Modeling Language, including Use Case, Activity, Sequence, and Class Diagrams. The system was implemented using Laravel, Filament, and Fortify, with role-based access for Admin and User/Sales. The proposed system integrates marketing data, document management, requests, and notifications within a centralized portal. Black Box Testing was conducted on authentication, data access, data management, request processing, notifications, and access control functions. The testing involved 19 functional scenarios, and all scenarios produced results consistent with the expected outputs. The system provides a structured platform for improving marketing data accessibility, retrieval efficiency, data control, and internal information management at CV San Amerta Romora.